Unveiling awareness and perception patterns: a comprehensive analysis of PM SVA Nidhi for street vendors in Meerut - Saini, Ashu; Fariya; Agarwal, Monika; Kumar, Parveen; Chauhan, Richa; Singh, Lata Surendra Prasad (Journal of Social Economics Research, 2024)
The vendors on the street are unorganized. They are solitary workers who rely on the sale of goods and services on urban streets to support their livelihoods. Many people sacrificed their jobs during the COVID-19 pandemic lockdown, and these people faced many issues for survival. To uplift their livelihood, the Government of India & Ministry of Housing and Urban Affairs introduced the scheme “Pradhan Mantri Street Vendor’s Atmanirbhar Nidhi Yojana (PM–SVA Nidhi)” on June 01, 2020. This paper attempts to study the awareness and perceptions regarding the implementation of the PM SVA Nidhi Yojana for street vendors in Meerut City. A total of 150 street vendors from Meerut were selected with the help of a convenience sampling technique. The latent constructs are described using the partial least square structural equation modeling (PLS-SEM) approach, with sufficient empirical support for the hypothesized correlations between awareness and perception. The study’s outcome revealed that there is a significant relationship between the awareness and perception of street vendors concerning the PM-SVANidhi scheme. Insights into awareness and perception patterns among street vendors could affect communication theories, such as how information spreads and influences behavior in underserved communities. The study reveals the awareness and perception patterns among street vendors. Policymakers can use these insights to enhance the scheme’s effectiveness.